PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR SISWA PADA MATERI BENTUK ALJABAR - Angel Madonsa; Cori Pitoy; Santje M Salajang (LPPM Universitas Bina Bangsa, 2023)
This research aims to find out that the average learning outcomes of students who study using the Think Pair Share (TPS) learning model are higher than the average learning outcomes of students who study using the Direct Instruction (DI) learning model. The population of this study were all class VII students at Garuda Manado Middle School. The samples taken in this research were class VIIA as the experimental class and class VIIB as the control class. Data analysis to test the hypothesis that the average learning outcomes of students studying algebraic material who studied using the TPS learning model were higher than the average learning outcomes of students who studied using the DI learning model, was carried out using the t-test with a significance level of α = 0.05. The value obtained is t_count = 3.75 > t_table = 1,729, thus it can be concluded that the average learning outcomes of students who study using the TPS learning model are higher than the average learning outcomes of students who study using using the DI learning model